Pendampingan Strategi Pemasaran dan Branding Industri Pabrik Tahu di Kelurahan Pinangsori - Pasaribu, Kurna Arifah; Pane, Ira; Suganda, Hikmah Anum (Cattleya Darmaya Fortuna, 2025)
Tofu is a traditional Indonesian food made from soybeans which are rich in protein and make a healthy food. In its activities, there are problems faced by this tofu business, namely the distance between the tofu production site and the market and the high price of soybeans is a problem faced by Mrs. Rahma Br.Lubis as the owner of the tofu factory, Neighborhood VII, Sidodadi Village, Pinangsori Sub-district Village, Tapanuli Tengah. The purpose of this service is to provide tofu production training for housewives and marketing strategy training as well as solutions to tofu owners for existing problems. In this court using qualitative methods, field observations, interviews, and documentation studies. Overcoming the problem of rising prices of soybeans as the main ingredient for making tofu, there are several alternative solutions including reducing the size of tofu and reducing the use of soybeans by replacing soybeans with non-soy beans. The five strategies offered to the owner of the tofu factory are: (1) Maintaining the quality of the product owned by the factory's taste, namely a natural taste without preservatives that has high nutritional value (2) Continue to establish good cooperation with soybean producers to meet factory production needs (3) Increasing promotional activities by posting on social media (4) Giving trust to others to manage the business to open factory branches in other regions (5) Updating production machines so that production run more effectively.